2006
DOI: 10.1016/j.jpsychores.2005.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of belief in “psychic healing” on self-reported pain in chronic pain sufferers

Abstract: Results suggest that anecdotal reports of effective psychic healing and "faith healing" are attributable to the power of belief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…Mean Healing Belief scores and mean change in General Health Questionnaire and McGill Pain Questionnaire, by condition.interesting considering that expectancy at some level seems to have an effect, but is not contingent on one's belief in the possibility or efficacy of distant healing. This result is not in line with the findings of Lyvers et al[8] who found that belief did correlate with outcome measures. In both the current study and Lyvers et al the McGill Pain Questionnaire was used, however belief measures for Lyvers et al were developed specifically for the study and may be a more accurate determinant of belief than those used in the current study.…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…Mean Healing Belief scores and mean change in General Health Questionnaire and McGill Pain Questionnaire, by condition.interesting considering that expectancy at some level seems to have an effect, but is not contingent on one's belief in the possibility or efficacy of distant healing. This result is not in line with the findings of Lyvers et al[8] who found that belief did correlate with outcome measures. In both the current study and Lyvers et al the McGill Pain Questionnaire was used, however belief measures for Lyvers et al were developed specifically for the study and may be a more accurate determinant of belief than those used in the current study.…”
contrasting
confidence: 96%
“…More relevant to the present study was the post hoc finding that participants' beliefs as to whether or not they were receiving healing appeared to be related to mental and physical improvements: those who believed that they were receiving healing had more positive outcomes. Additionally, Lyvers and colleagues [8], who conducted a double-blind study with twenty volunteers, found that pre-treatment questionnaires of belief in psychic healing and paranormal phenomena significantly correlated with positive outcomes irrespective of participants' treatment condition. The present study uses a partially blinded design: half of the participants were informed whether or not they would be receiving healing (not masked) and half were not (masked).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological effects, such as participants' expectation of AA treatment and participants' trust in the provider, may modulate the outcome of the study. 30 We believed that the placebo effect was shown in participants of the placebo control group and resulted in the reduction of VAS scores in that group as well. This study measured PT with the VAS to collect objective data related to minimizing unrelated pain factors such as psychological reasons.…”
Section: Discussionmentioning
confidence: 97%
“…Studies in medicine, surgery, or psychotherapy aim to distinguish a treatment effect from a placebo effect that is in part the effect of beliefs in or expectations for a given intervention. Yet, some studies on faith matters, most notably on faith healing, have employed such a design (Lyvers, Barling, & Harding-Clark, 2006;Masters 2005). Still, more attention should be paid to meanings and functions, as well as the complexity, of faith matters in individuals and groups.…”
mentioning
confidence: 99%